Analisis Rasio Kemandirian, Efektivitas dan Efisiensi Pendapatan Asli Daerah pada Laporan Realisasi Keuangan Kabupaten Garut - Oktaviani, Emilia; Marini, Yushita (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
This research aims to determine financial performance in Garut Regency by analyzing the independence ratio, effectiveness ratio and efficiency ratio of Regional Original Income (PAD) in the Financial Realization Report of the Regional Government Budget in Garut Regency. The Independence Ratio is carried out to measure the extent to which Garut district can generate its own income without depending on external sources of income. The effectiveness and efficiency ratio measurement is used to evaluate the extent to which the Garut Regency Regional Revenue and Expenditure Budget (APBD) is used optimally to achieve development goals. Data analysis will use the descriptive statistical method with data originating from the Garut Regency Government Budget Financial Realization Report for the period 2017 to 2021. The results of the research show that Garut Regency experienced a decline in financial independence between 2017 and 2018, but increased in 2019 to 2021 which influenced by the instructive relations of the central government. Financial effectiveness was below 100% from 2017 to 2019, but rose above 100% in 2020 to 2021. Financial efficiency from 2017 to 2019 was less than 100%, rose to more than 100% in 2020, then fell again by 99. 25% in 2021, indicating the need to adjust spending to income, maximize potential original income and optimize potential sectors to maintain better financial stability of the Garut Regency government.